Reference standards for the 6-min walk test in Croatian older adults - Sagat, Peter (Frontiers in Physiology, 2023)
The 6-min walk test (6MWT) is commonly used to assess the level of functional capacity of individuals with respiratory diseases. Although previous evidence has provided reference standards for the 6MWT in unhealthy older adults, no data have been provided for the Croatian healthy older populations. Therefore, the main purposes of the study were to define sex-and age-specific references for the 6MWT in older adults. Six-hundred and forty-three older adults (260 men and 383 women) aged 60-80 years were recruited in this observational cross-sectional study. The participants were instructed to walk the maximal distance possible for six minutes.The main outcome was the final score in the 6MWT conducted at a 30-m straight corridor. Men exhibited longer walking distance, compared to women (678.3±59.1 vs. 653.8±49.9 m, p < 0.001) and younger men and women performed better, than their older counterparts (p < 0.001).However, the sex*age interaction effect showed no significant differences between men and women in the same age range (p = 0.865). This is the first study with the purpose of providing reference standards for the 6MWT in a large sample of Croatian older adults. Older men and women in lower percentiles may be treated as a "risky group" of individuals with a special attention of implementing interventions to enhance the performance.